Запах жертвы: роман / Лев Пучков - Пучков Лев Николаевич (Спецназ, 2002)
Экземпляры: ф.2 (2003) / Инвентарный номер: 47441 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: П 90 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44